A Prospective on Zelinsky's Hypothesis of the Mobility Transition. Issue 4 (1st October 2018) - Cooke, Thomas J.; Wright, Richard; Ellis, Mark
Abstract: Wilbur Zelinsky's 1971 paper in Geographical Review entitled the "Hypothesis of the Mobility Transition" was both forward‐looking and offered innovative ideas regarding human geographic mobility. One of the most interesting aspects of the paper was a set of predictions for mobility in a "future superadvanced society". Many of these predictions have now come to pass, including a general decline in international and internal migration and residential change, the increasing regulation of migration ‐ especially internally, and the possibility that the widespread adoption of information and communication technologies has impacted human geographic mobility. Hence, this essay looks at the mobility transition not as an obsolete frame of reference but as a prescient, pliable, and adaptable framework which not only informs the study of human geographic mobility today but also, perhaps, even into the future.